Validitas dan Praktikalitas Media Pembelajaran Berbasis Video Tutorial pada Mata Kuliah Praktikum Instalasi Perumahan - Qasadina, Aprila Marisa; Pulungan, Ali Basrah; Setyawan, Herlin (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
— In residential installation learning the learning process is still centered on the lecturer (lecturer-centered learning) so that it results in the atmosphere in the room feeling boring and the material cannot be played repeatedly This is a fundamental problem of learning strategies, so students get less understanding of the material being taught. It also has an impact on the completion of the Electrical Practicum subject value. So the aim in this study is to develop a video tutorial learning media that is valid and practical to be used by students and lecturers in the learning process of residential installation. The model used in this research refers to the Luther-Sutopo version of the MDLC (multimedia development life cycle) method. The MDLC development model consists of 6 stages, namely, concept, design, material collection, manufacture, trial stage, distribution. The results of this study categorised video tutorial media as very valid, obtained from the results of validation by 86% media expert lecturers, and 94% material experts. Video tutorial media is categorised as very practical, obtained from the results of practicality by course lecturers of 95% and by students of 84%. So it can be concluded that the video tutorial-based learning media is very valid and practical to use in the housing installation learning process.